Children's Education According to Hadith - Moh. Husni Milki Q; Badri Khaeruman (UIN Sunan Gunung Djati Bandung, 2021)
This study aims to determine the education of children according to the hadith. This research is a qualitative type of research using literature study. The results and discussion of this study include an overview of children's education, hadith about children's education, and the concept of child education according to hadith. This study concludes that children's education is an individual formation of a child that aims to develop its potential. Providing education to a child must be accompanied by the ability of educators to see the abilities and skills of a child, because when a child grows up and develops according to his abilities and skills, that is where educators can be said to be successful. According to the hadith there are three basic principles in children's education, namely monotheism, worship, and morals, all three must go hand in hand in educating children. But the most important thing in children's education is the family, because the family is the one who understands the development and abilities of children. This research is expected to have beneficial implications for Muslims, especially families and Islamic educational institutions. This study has limitations, especially in the presentation of hadith about children's education so that it requires further research through a contextual approach.